2021
DOI: 10.1080/24748668.2021.1903249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of numerical unbalance constraints on workload and tactical individual actions during ball possession small-sided soccer games across different age groups

Abstract: This study aimed to examine the effects of age group (under-11, under-15, and under-23) on the external, internal workloads, and tactical individual actions when playing 4v2, 4v4, and 4v6 ball possession small-sided soccer games. Data were analysed separately under the opponent perspective (4vX) and by the cooperation perspective, according to teammates (4v2+X). For all opponent formats, statistical differences were found for walking, with older age groups covering longer distances. Higher running distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…[33], it was observed that individual play is used more frequently on the playing field, especially in the minor categories (Sub 9). These results align with the findings of Nunes et al [63], who identified that at early ages personal actions prevail over collective actions, a product of the dispersion and static position of the players. Age influences the tactical disposition on the playing field, specifically, the minor categories tend to extend longitudinally on the field, advancing quickly from goal to goal [62].…”
Section: Discussionsupporting
confidence: 92%
“…[33], it was observed that individual play is used more frequently on the playing field, especially in the minor categories (Sub 9). These results align with the findings of Nunes et al [63], who identified that at early ages personal actions prevail over collective actions, a product of the dispersion and static position of the players. Age influences the tactical disposition on the playing field, specifically, the minor categories tend to extend longitudinally on the field, advancing quickly from goal to goal [62].…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, it offered a highly controlled mechanism to ensure that all players conducted a standardised external load free from extraneous variables such as positional demands and/or reactive involvements with or without the ball. Previous studies observing load-response in adolescent soccer have utilised regular training (M. Wright et al, 2020;Wrigley et al, 2012) or SSG match-play (Hauer et al, 2021;Köklü et al, 2011;Nunes et al, 2021;Rowell et al, 2018), which may have increased the variables that influence external loads and thus the standardised dose.…”
Section: Discussionmentioning
confidence: 99%